2019
DOI: 10.1080/21645515.2019.1607132
|View full text |Cite
|
Sign up to set email alerts
|

Is the function of the HBeAg really unknown?

Abstract: The immune response to the hepatitis B virus (HBV) vaccine in newborns of hepatitis B e antigen (HBeAg)-positive or HBeAg-negative mothers is the subject of Huang et al. The authors report no correlation between the HBeAg status of the mothers/cord blood and the newborns immune response to the vaccine, but, unfortunately, draw unfounded conclusions regarding the tolerogenic potential of in utero exposure to HBeAg. In this reply, I address the possible influence of in utero exposure to the HBeAg, and briefly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…In the HBV life cycle, HBeAg is not essential for viral infection, replication and cccDNA formation. However, e antigen is a pan-orthohepadnavirus conserved product which is considered as an essential immune-modulator contributing to establish persistent viral infection [ 33 ]. Clinically, HBeAg is an important diagnostic marker for CHB clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…In the HBV life cycle, HBeAg is not essential for viral infection, replication and cccDNA formation. However, e antigen is a pan-orthohepadnavirus conserved product which is considered as an essential immune-modulator contributing to establish persistent viral infection [ 33 ]. Clinically, HBeAg is an important diagnostic marker for CHB clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…Opinions diverge upon the functional significance of HBeAg in the biology of HBV, but its main contribution is probably the induction of immune tolerance against HBeAg and HBcAg in newborns of HBV-infected mothers [40]. This function is obviously so central to the biology of HBV-like viruses that it is conserved in most Hepadnaviridae species [40], although recently several HBeAg-negative species were identified in shrews [41]. Nevertheless, HBeAg is the most important marker of reduced immune reactivity during the highly replicative phase of HBV infection, while HBcAg is the strongest T and B cell antigen expressed by HBV [42].…”
Section: Alternative Names For Hbv Antigens?mentioning
confidence: 99%
“…12 Dr. Milich agreed on Hsu et al's explanation that the unresponsiveness was resulted from immune tolerance to HBeAg/HBcAg at the T-cell level, because of HBeAg exposure in utero. 1 However, we think that this conclusion was somewhat far-fetched, because those healthy and HBeAgunexposed neonates also had no responsiveness to HBcAg. It was likely that the unresponsiveness in HBeAg-exposed neonates was associated with the cord blood T cells not primed by HBcAg in utero, as in utero HBV transmission very rarely occurs.…”
mentioning
confidence: 91%
“…We appreciate Dr. Milich's comments on our article recently published in Human Vaccine & Immunotherapeutics, 1 in which we concluded that the transplacentally acquired maternal hepatitis B e antigen (HBeAg) in utero appears not inducing immunotolerance to hepatitis B virus (HBV) and may be not associated with the pathogenesis of chronic HBV infection after neonatal exposure to HBV, based on the findings of similar levels of antibody response to hepatitis B vaccination between infants with and without fetal exposure to maternal HBeAg and between infants with relatively high and low fetal HBeAg exposure respectively. 2 Dr. Milich considered that our conclusion is not supported by our findings, because we did not directly measure the immune tolerance to HBeAg in HBeAg-exposed and -unexposed infants and did not determine the chronic HBV infection rate in infants born to HBeAg-positive and -negative mothers in the absence of immunoprophylaxis.…”
mentioning
confidence: 98%
See 1 more Smart Citation